The effect of video based mobile learning on students' writing skill - Asra, B.; Siregar, A.; Siraj, Saedah (2011)
Mobile learning is as the acquisition of any knowledge and skills in the process of learning and teaching for accessing the communications and multimedia such as video as the main tool through using mobile and technology, anywhere, anytime, The facilitate device has been helping the activity of teaching for teachers, especially teachers teaching English in secondary schools as well as facilitate and accelerate the acceptance of students, A study conducted to find out the effects of video based mobile learning on students' writing skills in Indonesia and examined limits on contents and mechanics in writing and module used in the English book at grade 10, The participant of the study is 80 students, The data was analyzed using descriptive and inferential statistics, Inferential statistics was used means, standard deviations and t-test. The video based mobile learning has supported teachers in encouraging students to use higher order thinking skill to solve problems that are relevant to their daily lives. It has allowed students to assess, and they can share their learning in home by mobile learning.